2008
DOI: 10.1111/j.1365-2648.2008.04634.x
|View full text |Cite
|
Sign up to set email alerts
|

School‐based drama interventions in health promotion for children and adolescents: systematic review

Abstract: There is a need for well-designed and theory-based studies that address drama interventions in health promotion for children and families. The challenge is to find or develop a theory, which combines educational, drama and health theories with valid and reliable measurements to examine the effects of the intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 37 publications
1
76
0
3
Order By: Relevance
“…The concept of socio-constructive learning stresses the development of identity and the perception of goals' values. A long-term goal in drama education is to help learners understand themselves, others and the world in which they live (see Bowell & Heap, 2001;Heikkinen, 2002;Joronen et al, 2011;Joronen et al, 2008;Laakso, 2004).…”
Section: Drama Education and Creativitymentioning
confidence: 99%
“…The concept of socio-constructive learning stresses the development of identity and the perception of goals' values. A long-term goal in drama education is to help learners understand themselves, others and the world in which they live (see Bowell & Heap, 2001;Heikkinen, 2002;Joronen et al, 2011;Joronen et al, 2008;Laakso, 2004).…”
Section: Drama Education and Creativitymentioning
confidence: 99%
“…Increasingly, healthcare administrators and designers have tried to exploit this relation; the arts figure in the aesthetic design of healthcare spaces and in the delivery of many interventions (Dose, 2006;Macnaughton, White & Stacy, 2005;SAH, 2009). There is a growing body of evidence supporting the use of art, arts-based interventions and art therapy to improve a range of health-related outcomes (Daykin, Byrne, Soteriou & O'Connor, 2008;Gold, Solli, Kruger & Lie, 2009;Gold, Voracek & Wigram, 2004;Goyal & Keightley, 2008;Joronen, Rankin & Astedt-Kurki, 2008;Maratos, Gold, Wang & Crawford, 2008;Stuckey & Nobel, 2010;Treurnicht Naylor, Kingsnorth, Lamont, McKeever & Macarthur, 2010;Wood, Molassiotis & Payne, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research into preventing childhood obesity has found that it can be difficult to engage parents in order to affect change within the family; 22,23 thus, we believed that the delivery methods needed to be sufficiently dynamic, creative and empowering to motivate the children to talk about the activities at home with their parents and encourage parents to come into the school to attend key events. This thinking led us to explore the use of interactive drama, as it had shown promise in promoting positive attitudes towards a number of health behaviours 24 and was a means of delivering a range of behaviour change techniques in manner that could engage the children.…”
Section: Rationale For Helpmentioning
confidence: 99%